PHRASEOLOGICAL WORDING OF THE CONCEPT OF "YOUTH" IN ENGLISH LITERARY DISCOURSE (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
In this article, the phraseological verbalization of the concept of "Youth" in English literary discourse is analyzed based on cognitive and linguistic approaches. The study investigated the semantic, stylistic and conceptual features of phraseological units related to the concept of youth used in works of fiction of different periods of English literature. As a result of the analysis, it was found that the concept of "Youth" is expressed in English linguistic culture through cognitive signs such as energy, vitality, perspective, inexperience, freedom, romance, and self-awareness. It was also shown that phrasal units such as "young blood", "young at heart", "in the bloom of youth", "young gun", "youth is wasted on the young" represent different semantic layers of the concept. The results of the research are important in the verbalization of concepts in artistic discourse and in illuminating the linguocognitive capabilities of phrasing units.
Keywords: concept, concept of youth, phrasing unit, artistic discourse, linguistic linguistics, cognitive linguistics, verbalization, English literature.